Measurement of Rotorcraft Blade Deformation Using Projection Moiré Interferometry - Gary A. Fleming; Susan Althoff Gorton (Shock and Vibration)
Projection Moiré Interferometry (PMI) has been used to obtain near instantaneous, quantitative blade deformation measurements of a generic rotorcraft model at several test conditions. These laser-based measurements provide quantitative, whole field, dynamic blade deformation profiles conditionally sampled as a function of rotor azimuth. The instantaneous nature of the measurements permits computation of the mean and unsteady blade deformation, blade bending, and twist. The PMI method is presented, and the image processing steps required to obtain quantitative deformation profiles from PMI interferograms are described. Experimental results are provided which show blade bending, twist, and unsteady motion. This initial proof-of-concept test has demonstrated the capability of PMI to acquire accurate, full field rotorcraft blade deformation data.